A computerized allocation model for assigning traffic policeman : a case study in Bangkok - Ahmed, Yusuf; Yordphol Tanaboriboon; Nagarur, Nagendra N.; Mori, Hiroshi; Government of Norway (Bangkok : Asian Institute of Technology, 1992)
The traffic conditions in Bangkok Metropolitan is deteriorating at an alarming rate. With the phenomenal increase in the number of vehicles, Bangkok Traff.ic Polir.8 are facing acute problems in s hortages of manpower and budget . Thus , it is very essential to allocate the duties of traffic policemen efficiently so as to minimize the manpower required. The ma in aim of this study is to develop a user friendly package that integrates the three components of workforce management system . The three components of workforce management system , i.e . allocation of traffic policemen to minimize the workforce required, cyclic and rotating daily s hift pattern and formulation of day-off pattern are proposed. Allocation of traffic policemen is achieved by a mathematical model with overlapping shifts , where demand fluctuations during a s hift are reflected by work intervals. The integer programming solution determines the staff al located at the beginning of each work interval. He uristic procedures are proposed to solve the problems, when either the required workforc e determined by mathematical mooel is greater than the available workforce in the police station, or the r equired workforce is less tha n or equal to available workforce. Thereafter , daily shift and day-off patterns are developed . The package so developed integrates all the three components of workforce management system. The program accepts the information required to run the model in a user friendly manner , loads the XA linear programming package to determine the required workforces and develops daily shift and day-off patterns . The software can be implemented to assist the traffic policemen in developing schedules for any police station .
Thesis (M.Eng.) - Asian Institute of Technology
A thesis submitted in partial fulfillment of the require ments for the degree of Master of Engineering, School of Engineering and Technology
Keywords: Traffic police -- Thailand -- Bangkok -- Data processing